MENINGKATKAN HASIL BELAJAR PADA POKOK BAHASAN MENYIMAK TEKS CERITA RAKYAT MELALUI PEMBELAJARAN PROBLEM POSING SISWA KELAS V SDN 2 MADUKORO - Kristina, Marilin; Dewi, Novi Ayu Kristiana; Ponidi, Ponidi; Muzayyana, Lucky (LPPM STKIP PGRI Bandar Lampung, 2019)
Based on the value of the results of Indonesian language learning students at SD Negeri 2 Madukoro class V odd semester on the subject of listening to folklore, the average daily test score of students is 65 and those who get a value of ≥ 70 as much as 68.97%. This shows that the Indonesian language learning outcomes of students are still relatively low because they are still under 70. This is due to a lack of student participation in the learning process, it is characterized by students who ask less, some students do not concentrate when learning takes place . Therefore, it is necessary to make efforts to overcome the problem, namely by using the problem posing learning model. This study aims to determine whether there is an increase in student learning outcomes through the problem posing learning model on the subject of listening to folklore text texts of fifth grade students of SD Negeri 2 Madukoro. The data in this study are quantitative data obtained through observation, field notes and tests at the end of each cycle. The results of this study indicate an increase in learning outcomes per cycle. The learning outcomes obtained in cycle 1 with an average value of 67.41 with students who obtained a value of ≥70 as much as 41.37% of 29 students, while in the second cycle the results of student learning which scored ≥70 reached 89.56% of 29 students. It can be concluded that the problem posing learning model can improve student learning outcomes on the subject of listening to folklore texts.